Perception of Semi-Professionals in using ICT in Manipal Academy of Higher Education Libraries - Rao, Ashish Kumar; Rao, Mahabaleshwara; Bhat, Shivananda Kukdel (DESIDOC Journal of Library & Information Technology, 2018)
Application of Information and Communication Technology (ICT) is one of the best practices observed in libraries as it enables automation and modernisation of library services. Today’s environment is digitally driven and library semi-professionals play an important role in providing up-to-date information to the users using modern technologies. The objective of the present study was to assess the perception of semi-professionals with respect to the use of ICT in Manipal Academy of Higher Education Libraries by them. 58 Library Assistant working in the seven constituent institutional libraries of MAHE at Manipal campus were included in the study and data were collected using questionnaire. The findings of the study revealed that EasyLib, the library automation software, and Electronic Public Access Catalogue (EPAC) had most impact on the role of semi-professionals (84.2 %) in providing ICT enabled services to the users. More than thirty percent (31.5 %) of the semi-professionals were of the opinion that ICT has considerably changed their duties and responsibilities. Semi-professionals are also of the opinion that they are now in a position to provide faster, more accurate and up-to-date information services to the users in their libraries. The findings of the present study support a need to implement the appropriate technologies in the libraries as they support the semi-professionals in their library housekeeping activities as well as in providing effective library services to the users.